Analytical Solutions of the Schrödinger Equation with Kratzer-screened Coulomb Potential for a Quarkonium System (Bulletin of Pure and Applied Sciences – Physics, 2021)
In this work, we obtain the Schrödinger equation solutions for the Kratzer potential plusscreened Coulomb potential model using the series expansion method. The energyeigenvalues is obtained in non-relativistic regime and the corresponding unnormalized eigenfunction. Three special cases were obtained. We applied the present results to calculateheavy-meson masses of charmonium ܿܿ̅ and bottomonium ܾܾത, and we got the numericalvalues for1S, 2S, 1P,2P, 3S, 4S ,1D,2D and 1F states. The results are in good agreement withexperimental data and the work of other researchers.